Malaria causing post-infectious cerebellitis, a case report and literature review. (September 2022) - Hijazi, Mohamad; Abdalla, ELMustafa; Fadul, Abdalla; Eltayeb, Doaa Ahmed; Al-Mashdali, Abdulrahman
Abstract: Background: Malaria is a common parasitic infection with a wide range of clinical presentations. Thus, it should be suspected for any symptomatic patient with a recent travel history to a malaria-endemic area. Case presentation: In this case report, we will present a previously healthy 28-year-old patient who developed cerebellar signs that were attributed to infectious etiology later on proven to be a malaria-related complication that responded well to anti-malarial medications. Discussion: The classical presentation of malaria with attacks of fever is noticed only in around 60% of the patients. The development of immunity, the increasing resistance to anti-malarial drugs, and the indiscriminate use of anti-malarial drugs have led to malaria presenting unusual characteristics. Cerebellar ataxia, extrapyramidal signs, and various psychiatric manifestations have been described as early presentations of cerebral malaria or as a part of the post-malaria neurological syndrome. Other neurological syndromes like peripheral neuropathies, movement disorders, myelopathies, and stroke-like syndrome have also been described. Conclusion: Malaria should be included as a differential diagnosis in a patient presenting with cerebellar signs as its devastating if left untreated. However, it responds well to anti-malarial regimens if started early during the course. Highlights: Malaria can cause a wide range of neurological manifestations. Plasmodium falciparum is the one associated with sever presentations. Post-infectious cerebellitis can be caused by malaria. Cerebellitis usually respond well to malaria treatment.